2008
DOI: 10.3129/i08-145
|View full text |Cite
|
Sign up to set email alerts
|

Expression of integrins in human proliferative diabetic retinopathy membranes

Abstract: Background-The process of identifying molecules that regulate angiogenesis is critical to the success of candidate therapies for ocular neovascular disease. The purpose of the study was to determine the pattern of expression for integrins and their colocalization with endothelium in membranes from proliferative diabetic retinopathy (PDR).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Integrins, such as a v b 3 , a v b 5 , a 5 b 1 and a 2 b 1 , promote angiogenesis by mediating cell migration, proliferation and survival of angiogenic endothelial cells [133]. Recently, we demonstrated that only a v b 3 integrin was expressed in PDR epiretinal membranes and was specifically localized in vascular endothelial cells and stromal cells [17]; similar findings were noted by Ning et al [134]. Integrin a v b 3 has been especially identified as a marker of angiogenesis because it is expressed on angiogenic blood vessels in human wound granulation tissue but not in normal skin.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…Integrins, such as a v b 3 , a v b 5 , a 5 b 1 and a 2 b 1 , promote angiogenesis by mediating cell migration, proliferation and survival of angiogenic endothelial cells [133]. Recently, we demonstrated that only a v b 3 integrin was expressed in PDR epiretinal membranes and was specifically localized in vascular endothelial cells and stromal cells [17]; similar findings were noted by Ning et al [134]. Integrin a v b 3 has been especially identified as a marker of angiogenesis because it is expressed on angiogenic blood vessels in human wound granulation tissue but not in normal skin.…”
supporting
confidence: 68%
“…Its expression increased during angiogenesis on the chick chorioallantoic membrane. In the latter assay, a monoclonal antibody to a v b 3 blocked angiogenesis induced by basic FGF, TNF-a and human melanoma fragments but had no effect on pre-existing vessels [134]. Ligation of integrin a v b 3 is required for the survival and maturation of newly forming blood vessels.…”
mentioning
confidence: 99%
“…Only αvβ3 and β3 integrin proteins were found to be moderately induced and specifically co-localized with endothelial cell markers in two of the four patients with PDR tested. While further validation is required, these data suggest a specific impact of PDR on a subset of integrins, which could reflect their role in pathological angiogenesis [21] . Perturbations of the retinal vasculature associated with diabetes have long been known from animal models, but studies using tissues from human donors continue to be key to our understanding of the molecular mechanisms underlying the vascular changes associated with the different stages of DR.…”
Section: Neo-angiogenesismentioning
confidence: 92%
“…A study conducted by Friedlander et al [20] in animal models of angiogenesis suggested that since αvβ3 and αvβ5 integrins were involved in angiogenesis, these specific integrins could be critical in PDR. Ning et al [21] utilized this data to expand upon and determine the co-localization of five different integrins with the retinal vascular endothelium of four patients with PDR. Contrary to what was found in the animal models, no staining was observed for αvβ5 integrins, possibly attributed to inter-species variability.…”
Section: Neo-angiogenesismentioning
confidence: 98%
“…A number of studies have shown that integrins are implicated in pathologic angiogenesis in the retina. Integrin α v β3 has been found localized in retinal neovascular tissue removed from patients with proliferative diabetic retinopathy 78. In the mouse model of OIR, inhibition of α v β3 and α v β5 using a nonpeptidic antagonist reduced neovascular area, and VEGF and VEGFR2 expression in the retina 79.…”
Section: Signaling Pathways Involved In Vegf Expression and Vegf-medimentioning
confidence: 99%